2015
DOI: 10.2174/1570162x1303150506181434
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Virological Outcomes of Patients Switched from LPV/r to ATV/r-Containing Second- Line Regimens

Abstract: Among patients that were switched to ATV/r-containing regimens, we found improvements in immunological responses and no increase in risk of virologic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…In our study, the rate of VF during virological suppression was low in patients who had undergone both minor and major ART switches. These results are consistent with prior studies that ART substitution in virologically suppressed HIV‐infected patients is generally effective .…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the rate of VF during virological suppression was low in patients who had undergone both minor and major ART switches. These results are consistent with prior studies that ART substitution in virologically suppressed HIV‐infected patients is generally effective .…”
Section: Discussionsupporting
confidence: 92%
“…Sample sizes for the included studies range from 40 patients enrolled by a study conducted in Uganda [40] to 6,714 patients enrolled by a study accomplished in Nigeria [41]. The study participants of 26 studies were adults [19, 2325, 27, 34, 40, 4260], while that of 2 studies [22, 61] and 5 studies [6, 41, 6264] were children and mixed age groups, respectively. Sixteen studies (n = 16) were from southern Africa [23, 27, 43, 4552, 57, 58, 60, 62, 64]; 7 studies were from eastern Africa [22, 34, 40, 53, 55, 61, 63]; 5 studies were from western Africa [25, 41, 42, 44, 54]; and 5 studies were from mixed regions in SSA [6, 19, 24, 55, 59].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies that reported higher rates of VF predominantly used LPV/r as the PI/r of choice [10, 29]. However, we do not expect differences in therapeutic responses to LPV/r versus ATV/r [30]. Improved access to second line ART in Malawi ([2], http://www.who.int/hiv/pub/guidelines/arv2013/download/en/) also may potentially explain the improved virological outcomes evidenced in this study.…”
Section: Discussionmentioning
confidence: 68%